KEAMANAN PENGGUNAAN OBAT PADA KEHAMILAN DI RUMAH SAKIT SWASTA YOGYAKARTA - Sari, Chynthia Pradiftha; Hanifah, Suci; Febrianti, Yosi; Sari, Azmi Fahma; Dwirahmania, Pipit (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Pregnancy is a special physiological condition in which the use of medication is often unavoidable. However, the risks of teratogenicity and drug safety require careful evaluation to minimize risks to both mother and fetus. This study aims to evaluate the safety of drug use based on FDA (Food and Drug Administration) categories in pregnant inpatients at a private hospital in Yogyakarta. The study uses a descriptive observational method with a cross- sectional design, analyzing 141 inpatient medical records from 2022. The analyzed data includes patient demographics, diagnoses, drug safety, and dosages. Inclusion criteria were pregnant inpatients treated with or without pregnancy emergencies; exclusion criteria were patients giving birth or experiencing abortion. Descriptive results (using Microsoft Excel) showed most pregnant inpatients were aged 20-35 years (80.14%), hospitalized during the first trimester (49.65%), had no comorbidities (90.07%), no emergency pregnancy conditions (82.27%), and a length of stay under 4 days (72.34%). The most common diagnosis was hyperemesis gravidarum (41.84%), with predominant use of multivitamins (16.18%) and antiemetics (14.91%). The safety of drugs in inpatients was categorized as A (18.80%), B (34.34%), C (36.86%), D (2.26%), and N (6.77%), with appropriate dosage usage (96,30%). The study concludes that drug use was dominated by category C, and no use of category X drugs was found. The most used drugs were folic acid multivitamins and iron supplements for increasing blood levels.